Mortality and morbidity profile of preterm very low birth weight infants: A prospective longitudinal observational study - Bansal, Anuradha; Chawla, Deepak (Indian Journal of Child Health, 2022)
Objective: To study the survival to discharge and immediate outcome of preterm very low birth weight (VLBW) infants. Materials and Methods: Design: Prospective observational longitudinal study. Setting: Level II neonatal intensive care unit in a tertiary care center. Subjects: All live born inborn babies with birth weight 401-1499 g or gestational age between 22 weeks 0 day and 31 weeks 9 days. Outcome: Key outcome was survival to discharge for preterm VLBW infants. Incidence of major morbidities was assessed. Results: Of 183 neonates enrolled in the study, 73.2% babies were alive at initial disposition. Respiratory distress syndrome was the most common morbidity, and infection was the most common cause of death. Lower gestational age and low APGAR score at 1 min were the most significant predictors of poor outcome. Conclusion: This study provides a baseline database for evaluating the efficiency of perinatal services in a tertiary care center. Further large-scale trials are needed to substantiate our findings and to study neurodevelopmental outcome of VLBW infants.